A study on micronucleus frequency in cervical smear as biomarker for genetic damage in polycystic ovarian syndrome - R., Showri; T., Rajini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Polycystic ovary syndrome (PCOS) is a multifactorial endocrine disorder with metabolic and reproductive consequences. Genomic damage and susceptibility to cancer are noteworthy concerns in PCOS. Relationship between PCOS and endometrial and ovarian cancer has already been established. The presence of high body mass index, excess triglycerides, oxidative stress and occurrence of metabolic syndrome is a frequent occurrence in PCOS. This may succeed into genetic damage and susceptibility to cervical cancer as they are also known risk factors of the same. The aim of the study was to estimate the frequency of micronuclei in cervical smear and to determine if it can be used as a biomarker of genomic instability and susceptibility to cervical changes in the future in PCOS. Methods: This observational case control study included 38 subjects diagnosed with PCOS by Rotterdam’s criteria and 38 controls and was conducted between September 2018 to March 2020 in VIMS and RC. Data regarding age and anthropometric details and cervical smear samples was collected from all the subjects. The frequency of micronuclei in cervical smears was expressed as mean±standard deviation (SD). Differences between the PCOS group and the control group were examined for statistical significance using two-sample independent t-test. A p value of ≤0.05 denoted statistically significant difference. Results: The mean±SD of micronuclei frequencies in cervical smears was observed to be 1.69±0.69 and 0.33±0.18 (p value <0.0001) in the subjects with PCOS and control group, respectively. Conclusions: Micronuclei frequency was found to be elevated in cervical smears of women with PCOS when compared to controls indicating genetic instability and probable susceptibility to cervical cancer in the future in women with PCOS.